A cluster–based multicast scheme with asymmetric link support in Mobile Ad hoc Networks. (23rd May 2012) - Su, Yi–Yu; Hwang, Shiow–Fen; Lu, Kun–Hsien; Dow, Chyi–Ren
Multicast in MANETs is an important issue, and most of existing multicast schemes are designed for networks with only bidirectional links and thus may become malfunction in networks with unidirectional links. In this work, we exploit unidirectional links and employ the clustering technique to design an efficient multicast scheme with asymmetric link support in MANETs. By detecting and utilising unidirectional links, the performance of multicasting in MANETs with unidirectional links is improved. Simulation results demonstrate that the proposed scheme achieves higher delivery ratio and incurs relatively moderate control overhead with respect to that of ODMRP and ODMRP–ASYM.